Challenging the negative learning bias hypothesis of depression: reversal learning in a naturalistic psychiatric sample. Issue 2 (15th January 2022) - Brolsma, Sophie C. A.; Vrijsen, Janna N.; Vassena, Eliana; Rostami Kandroodi, Mojtaba; Bergman, M. Annemiek; van Eijndhoven, Philip F.; Collard, Rose M.; den Ouden, Hanneke E. M.; Schene, Aart H.; Cools, Roshan
Abstract: Background: Classic theories posit that depression is driven by a negative learning bias. Most studies supporting this proposition used small and selected samples, excluding patients with comorbidities. However, comorbidity between psychiatric disorders occurs in up to 70% of the population. Therefore, the generalizability of the negative bias hypothesis to a naturalistic psychiatric sample as well as the specificity of the bias to depression, remain unclear. In the present study, we tested the negative learning bias hypothesis in a large naturalistic sample of psychiatric patients, including depression, anxiety, addiction, attention-deficit/hyperactivity disorder, and/or autism. First, we assessed whether the negative bias hypothesis of depression generalized to a heterogeneous (and hence more naturalistic) depression sample compared with controls. Second, we assessed whether negative bias extends to other psychiatric disorders. Third, we adopted a dimensional approach, by using symptom severity as a way to assess associations across the sample. Methods: We administered a probabilistic reversal learning task to 217 patients and 81 healthy controls. According to the negative bias hypothesis, participants with depression should exhibit enhanced learning and flexibility based on punishment v. reward. We combined analyses of traditional measures with more sensitive computational modeling. Results: In contrast to previous findings, this sample of depressed patients with psychiatric comorbidities did not show a negative learning bias. Conclusions: These results speak against the generalizability of the negative learning bias hypothesis to depressed patients with comorbidities. This study highlights the importance of investigating unselected samples of psychiatric patients, which represent the vast majority of the psychiatric population.